2014
DOI: 10.1111/j.1532-950x.2014.12128.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation ofIn VitroMechanical Properties of Different Designs of Epoxy‐Pin External Skeletal Fixation Systems

Abstract: Overall, EC followed by EM-II epoxy-pin fixator designs had better mechanical strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…At 32°C ambient temperature, the maximum temperature (38°C) of the fast curing epoxy dough was attained at 4 to 5 minutes of polymerization. 29 In a comparative study, the maximum temperature recorded during curing of the epoxy resin (43°C) was less than the PMMA (98.5°C). 9 In an in vitro study on heat transfer from epoxy polymer and PMMA to fixation pins, the heat transfer from epoxy putty to the pins did not cause the temperature to reach 47°C (>47°C would cause thermal soft tissue injury) at any time, 30 indicating that epoxy resin is safe for use in external skeletal fixation systems at least 1 cm away from the skin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At 32°C ambient temperature, the maximum temperature (38°C) of the fast curing epoxy dough was attained at 4 to 5 minutes of polymerization. 29 In a comparative study, the maximum temperature recorded during curing of the epoxy resin (43°C) was less than the PMMA (98.5°C). 9 In an in vitro study on heat transfer from epoxy polymer and PMMA to fixation pins, the heat transfer from epoxy putty to the pins did not cause the temperature to reach 47°C (>47°C would cause thermal soft tissue injury) at any time, 30 indicating that epoxy resin is safe for use in external skeletal fixation systems at least 1 cm away from the skin.…”
Section: Discussionmentioning
confidence: 97%
“…This may be attributed to greater fixation strength achieved by joining the two connecting bars on either ends on both sides in multiplanar and circular configurations. 10,29 Joining of connecting bars might have minimized the translocation of pins and micromotion at the pin-bone interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…This versatility is very useful when treating distal RUF in miniature‐ and toy‐breed dogs because these fractures often have limited bone stock in the short distal fracture fragment. Pins placed at multiple angles in small bone fragments can add mechanical stability to the fixation . The freedom of pin placement also limits iatrogenic trauma to vital structures and reduces soft tissue impingement .…”
Section: Discussionmentioning
confidence: 99%
“…Some initial studies involving acrylic external skeletal fixators have revealed that the acrylic external skeletal fixator is stronger under axial, craniocaudal bending and torsional loading, and that it is as strong in mediolateral bending loads compared to a stainless steel equivalent (7). An in vitro study of an epoxy external skeletal fixator found circular and multiplanar configurations of fixators to be stronger under axial, bending and torsional loads, as compared to a uniplanar configuration (21). The aim of the present study was to evaluate and compare different configurations of acrylic external skeletal fixator systems based on the in vitro biomechanical properties so that better configurations can be used in routine clinical practice.…”
Section: Introductionmentioning
confidence: 98%